(3TQM OjhGf GdeJfHis - (3CHi GdbGSe EHQGgje Hf RcQjG GHf GdEadjdi GdbQWHis; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s ((3YHO Gddg eMeO (B( (3GdJLjHi (B) s)
(3ChdgG (B:s
(3WhGd bfG JWGYfgG bUGQ hbWQc aj fOi hhZi HMGQ s
(3BNQgG (B:s
(3aEPG eG GTJgi NdhOc OGYgG bGd (B: (3dGRGdJ Ch JQi dc eKdG s
(3bWYI ef BNQ GdLRAs
(3fSNI KGdKI JJab ai BNQgG eY BNQ GdfSNI GdChdi HGNJdGa HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs